2006
DOI: 10.1080/03601230600616957
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer and Cauliflower Mosaic Virus Promoter 35S Activity in Mammalian Cells

Abstract: The cauliflower mosaic virus 35S promoter (CaMV35s) is extensively used in genetically modified crops for human and animal consumption. Horizontal gene transfer is attracting particular attention, in light of experimental reports, showing the presence of dietary DNA into animal tissues. Health implications may derive from possible activities of the heterologous promoter in mammalian cells after integration in the host genome. To evaluate this hypothesis, in vivo and in vitro experiments were performed using GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Sequence overlap exists between P35S and the coding sequences of one CaMV gene, gene VI, also known as P6 (Figure 1), indicating the potential for virus protein expression in humans (Podevin and Du Jardin, 2012). Another concern is the horizontal gene transfer risk with DNA recombination that can potentially occur between P35S and human genes, along with the potential for P35S to facilitate expression of human genes (Chiter et al, 2000;Morel and Tepfer, 2000;Nielsen and Townsend, 2004;Paparini and Romano-Spica, 2006;Bawa and Anilakumar, 2012). In two studies that have attempted to address these concerns, no evidence was observed for the activity of the P35S promoter in mammalian cells (Vlasák et al, 2003;Paparini and Romano-Spica, 2006).…”
Section: Camv and Food Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence overlap exists between P35S and the coding sequences of one CaMV gene, gene VI, also known as P6 (Figure 1), indicating the potential for virus protein expression in humans (Podevin and Du Jardin, 2012). Another concern is the horizontal gene transfer risk with DNA recombination that can potentially occur between P35S and human genes, along with the potential for P35S to facilitate expression of human genes (Chiter et al, 2000;Morel and Tepfer, 2000;Nielsen and Townsend, 2004;Paparini and Romano-Spica, 2006;Bawa and Anilakumar, 2012). In two studies that have attempted to address these concerns, no evidence was observed for the activity of the P35S promoter in mammalian cells (Vlasák et al, 2003;Paparini and Romano-Spica, 2006).…”
Section: Camv and Food Safetymentioning
confidence: 99%
“…Another concern is the horizontal gene transfer risk with DNA recombination that can potentially occur between P35S and human genes, along with the potential for P35S to facilitate expression of human genes (Chiter et al, 2000;Morel and Tepfer, 2000;Nielsen and Townsend, 2004;Paparini and Romano-Spica, 2006;Bawa and Anilakumar, 2012). In two studies that have attempted to address these concerns, no evidence was observed for the activity of the P35S promoter in mammalian cells (Vlasák et al, 2003;Paparini and Romano-Spica, 2006). In terms of the potential for viruses to recombine with and acquire genes from transgenic plants (i.e., horizontal gene transfer from transgenic plants to a virus), earlier studies of CaMV have demonstrated that this is possible (Schoelz and Wintermantel, 1993;Wintermantel and Schoelz, 1996), but only under very specific conditions, such as strong selection pressure in the laboratory (Wintermantel and Schoelz, 1996).…”
Section: Camv and Food Safetymentioning
confidence: 99%
“…No disease or recombination with human viruses has ever been reported irrespective of the fact that humans have been ingesting high levels of CaMV and its 35S promoter (Paparini and Romano-Spica 2004). Recent studies conducted using mice as an experimental animal were unable to detect DNA transfer as well as transcriptional activity of the CaMV35S quantified through realtime PCR (Paparini and Romano-Spica 2006).…”
Section: Potential Risk Of the Introduced Gene Cassettementioning
confidence: 98%
“…In mammalian cells, transient expression of the transgenes transcribed by the CaMV35S promoter may possibly let the genes controlled by 35S promoter to express (Tepfer et al 2004). Contrary to this hypothesis, recent studies conducted using mice as an experimental animal, were unable to detect DNA transfer as well as transcriptional activity of the CaMV35S quantified through real time PCR (Paparini and Romano-Spica 2006). This area of research needs further explorations (Dona and Arvanitoyannis 2009).…”
Section: Potential Risk Of the Introduced Gene Cassettementioning
confidence: 93%